Prolonged shedding of SARS-CoV-2 at high viral load amongst hospitalised immunocompromised persons living with HIV in South Africa. (March 2022) - Meiring, S.; Tempia, S.; Bhiman, J.; Kleynhans, J.; Buys, A.; Makhasi, M.; Mcmorrow, M.; Moyes, J.; Quan, V.; Walaza, S.; Plessis, M. Du; Wolter, N.; et al.
Abstract : Purpose: There is limited information on SARS-CoV-2 shedding duration amongst persons living with HIV (PLWH). We hypothesised that PLWH shed SARS-CoV-2 for longer periods and at higher viral load than HIV-uninfected persons. Methods & Materials: From May through December 2020, we conducted a prospective cohort study at 17 hospitals in South Africa. Patients aged >18 years hospitalised with symptomatic COVID-19 were enrolled and followed up every two days with nasopharyngeal/oropharyngeal (NP/OP) swabs until cessation of SARS-CoV-2 shedding (two consecutive negative NP/OP swabs). Real-time reverse transcription polymerase chain reaction (rRT-PCR) testing for SARS-CoV-2 was performed and Cycle-threshold (Ct ) values <30 were considered a proxy for high SARS-CoV-2 viral load. Accelerated time-failure Weibull regression models were used to assess factors associated with prolonged shedding. Results: Of 2, 175 COVID-19 patients screened, 300 were enrolled and 258 individuals (156 HIV-uninfected and 102 PLWH) had >1 swabbing visit (median visits 5 (range 2-21)). Median time to cessation of shedding was 13 days (inter-quartile range (IQR) 6-25) and did not differ by HIV status. Among PLWH, when adjusting for CD4 count and obesity, those not currently taking antiretroviral therapy were more likely to have prolonged SARS-CoV-2 shedding (median 13 days (IQR 6-37) vs 10 days (IQR 4-22) on antiretroviral therapy, adjusted hazard ratio (aHR) 0.03, 95% confidence interval (CI) 0.002-0.38, p=0.007). Amongst a subset of 94 patients with initial respiratory sample Ct values <30, median time of shedding at a high SARS-CoV-2 viral load was 8 days (IQR 4-17). Adjusting for age and glucocorticoid use, PLWH with a CD4 cell count<200 cells/µl shed at high SARS-CoV-2 viral loads for longer (median 27 days, IQR 8-43, aHR 0.14, 95% CI 0.07-0.28, p<0.001), whereas PLWH with CD4 cell count>200 cells/μl shed at high SARS-CoV-2 viral loads for a similar time period (median 7 days, IQR 4-10, aHR 1.14, 95% CI 0.56-2.31, p=0.713), compared to HIV-uninfected persons (median 7 days, IQR 4-13). Conclusion: PLWH not on treatment or with CD4 cell count<200 shed SARS-CoV-2 for a longer duration and at a higher SARS-CoV-2 viral load than HIV-uninfected persons. Better HIV control may facilitate quicker clearance of SARS-CoV-2.